A comparison of decomposition the decoupling carbon emissions from economic growth in transport sector of selected provinces in eastern, central and western China. (20th August 2019) - Wang, Qiang; Wang, Shasha
Abstract: The transport sector is steadily becoming a new major source of carbon emissions in China. A better understanding of decoupling economic outputs from carbon emissions in the Chinese transport sector could facilitate the country's move to low-carbon transport. This study combines the Tapio decoupling model and Log Mean Divisia Index method to develop a decoupling effort model, in order to quantify the state of decoupling between economic outputs and carbon emissions, investigate the effects of carbon emissions, and evaluate these decoupling efforts in the transport sector of six provinces in eastern, central and western China. The results show that: (i) the eastern region had achieved stable decoupling; the development of the central and western regions was imbalanced, with frequent flux in their states of decoupling; (ii) the pattern of driving factor of transport carbon emissions in three eastern, central and western was similar. The economic scale effect was the primary contributor to carbon emissions, while the energy intensity effect was the main inhibitor. The influence of the carbon intensity effect and the population effect was found to be quite weak; (iii) the three economic regions had all undertaken efforts to achieve decoupling, with the eastern region ranking first in the extent of these efforts, and the western region ranking last; (iv) the energy intensity was a weak effect in decoupling effort, indicating that their energy utilization efficiency is not optimal, and that there still exists considerable room for improvement. Finally, some policy recommendations are proposed. Highlights: Combining Tapio model and LMDI to develop a decoupling effort model. Transportation sector of six provinces in eastern, central and western China were selected. The pattern of drivers of carbon emission in three eastern, central and western was similar. In decoupling efforts, the eastern>central>western China. The energy intensity effect was in a weak decoupling effort.